2021
DOI: 10.1111/pai.13540
|View full text |Cite
|
Sign up to set email alerts
|

Food allergic reactions during the Covid‐19 pandemic lockdown in Israeli children

Abstract: To the Editor, Coronavirus disease 2019 , the disease caused by severe acute respiratory syndrome coronavirus 2, has affected Israel along with most other nations during the current global pandemic.On March 19, 2020, a national state of emergency and lockdown was declared. 1 These events led to an extremely unusual situation in which children stayed only at home, with their primary caregiver. Therefore, we aim to determine the incidence, risk factors for food allergic reaction (FAR) and parental willingness to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, an Israeli survey found that the reported food allergic reactions during COVID-19 lockdown were lower than those in the previous 3 months. Young age, history of allergic reactions and allergy to multiple allergens were identified as risk factors for FA in preschool children ( 118 ). Proper management of FA during COVID-19, including FA diagnosis, FA prevention, management of anaphylaxis, oral food challenge and oral immunotherapy, has been discussed elsewhere ( 119 ).…”
Section: Food Allergymentioning
confidence: 99%
“…However, an Israeli survey found that the reported food allergic reactions during COVID-19 lockdown were lower than those in the previous 3 months. Young age, history of allergic reactions and allergy to multiple allergens were identified as risk factors for FA in preschool children ( 118 ). Proper management of FA during COVID-19, including FA diagnosis, FA prevention, management of anaphylaxis, oral food challenge and oral immunotherapy, has been discussed elsewhere ( 119 ).…”
Section: Food Allergymentioning
confidence: 99%